Patterns of kidney injury in pediatric nonkidney solid organ transplant recipients. Issue 6 (6th February 2018) - Williams, C.; Borges, K.; Banh, T.; Vasilevska‐Ristovska, J.; Chanchlani, R.; Ng, V. L.; Dipchand, A. I.; Solomon, M.; Hebert, D.; Kim, S. J.; Astor, B. C.; Parekh, R. S.
Abstract : The incidence of acute kidney injury (AKI) and its impact on chronic kidney disease (CKD) following pediatric nonkidney solid organ transplantation is unknown. We aimed to determine the incidence of AKI and CKD and examine their relationship among children who received a heart, lung, liver, or multiorgan transplant at the Hospital for Sick Children between 2002 and 2011. AKI was assessed in the first year posttransplant. Among 303 children, perioperative AKI (within the first week) occurred in 67% of children, and AKI after the first week occurred in 36%, with the highest incidence among lung and multiorgan recipients. Twenty‐three children (8%) developed CKD after a median follow‐up of 3.4 years. Less than 5 children developed end‐stage renal disease, all within 65 days posttransplant. Those with 1 AKI episode by 3 months posttransplant had significantly greater risk for developing CKD after adjusting for age, sex, and estimated glomerular filtration rate at transplant (hazard ratio: 2.77, 95% confidence interval, 1.13‐6.80, P trend = .008). AKI is common in the first year posttransplant and associated with significantly greater risk of developing CKD. Close monitoring for kidney disease may allow for earlier implementation of kidney‐sparing strategies to decrease risk for progression to CKD. Abstract : In an observational cohort study of 303 children after heart, lung, liver, or multiorgan transplantation, acute kidney injury occurs in approximately one‐third of children in the first year posttransplant and is associated with significantly greater risk of developing chronic kidney disease.